Systematic Literature Review of Customs Fees Through Schools of Economic Thought and their Role in Supporting the State Treasury - Shebl, Maather Timol; Jabbar, Yusra Rasim (South Asian Journal of Social Sciences and Humanities, 2023)
The goal of this research is to look at a variety of pertinent publications in order to contrast custom  duties with the function of the state treasury and develop future research issues. This article does  a systematic review of the literature on custom duty research published during 1990 and 2023. The  analysis takes use of Scopus data in addition to pertinent terms such as custom duties and the role  of state treasury. This complete literature evaluation was selected from 537 articles. This research  found that investing in customs duties is critical for assuring the prosperity of a nation. To enhance  customs duties and the role of the state treasury, it is vital to concentrate on critical topics that will  benefit the country's growth. Therefore, the role of the state treasury system and transparent  customs duties are critical for the nation sustainable development. This work established seven  research topics for future researchers following a review and analysis of the custom duty’s literature, enabling the research to be carried out.
Keywords: custom duties; state treasury role; sustainable development